CONTEMPORARY METHODS OF PSYCHOLOGICAL ASSISTANCE IN CONDITIONS OF UNCERTAINTY - Haba, Iryna (Personality and environmental issues, 2024)
The article examines contemporary methods of psychological assistance in conditions of uncertainty, which functions as a powerful stressor resulting from armed conflicts, pandemics, economic instability, and social crises. Theoretical foundations of intolerance of uncertainty (IU) are analyzed as a transdiagnostic mechanism that increases the risk of developing anxiety, depressive, and post-traumatic disorders. Evidence-based psychotherapeutic approaches are summarized, including cognitive-behavioral therapy (CBT), acceptance and commitment therapy (ACT), mindfulness-based programs, as well as art- and play-based methods (Hibuki therapy, sandplay therapy), which foster psychological flexibility, distress tolerance, and the integration of traumatic experience. Special attention is given to digital formats of assistance (online CBT, blended models, telemedicine), whose effectiveness has been confirmed by systematic reviews. The article also highlights special cases of applying innovative methods, such as remote EMDR in working with the consequences of mass traumatic events, as well as psychological support for high-risk groups.